Job satisfaction among health professionals in a District of North West province, South Africa - Reabetswe A. Mere; Thembi V. Simbeni; Mmampedi Mathibe; Ntlogeleng M. Mogale; Sam T. Ntuli (AOSIS, 2023)
Background: Job satisfaction has become an area of relevance and debate in public health as it is directly linked to staff absenteeism, retention and turnover of the workforce and as such, influences the organisational commitment of the workers and the quality of health services provided. It is therefore essential to discern what drives healthcare professionals to remain working in the public health sector. Aim: This study aimed to determine job satisfaction and its associated factors among healthcare professionals. Setting: North-West province South Africa. Methods: A cross-sectional study was conducted among 244 healthcare professionals of different categories in three district hospitals. A self-administered structured questionnaire with 38 questions to measure job satisfaction was used to collect data. The chi-square test was used to compare groups, and a p-value 0.05 was considered statistically significant. Results: Overall, 62% of the participants were not satisfied with their job. The most common factors that participants were not satisfied with include job security (52%), standard of care (57%), opportunity to develop (59%), payment or wages (76%), workload (78%) and working environment (89%). Job satisfaction was significantly influenced by age, job category and years of service. Conclusions: The predictors of job satisfaction include age, category of employees and years of service. Interventions are required to improve the degree of job satisfaction among health care professionals. Contribution: Findings of this study will assist informing plans that are geared towards enhancing healthcare worker job satisfaction, retention and consequent health systems strengthening.